Blackness as Delinquency - Cheryl Nelson Butler (Washington University Law Review, 2013)
This is one of the first law review article to analyze both the role of ―blackness‖ in shaping the first juvenile court and the black community’s response to the court’s jurisprudence. This Article breaks new ground on two fronts. First, it considers the first juvenile court’s treatment of black youth within the context of the heightened racial oppression immediately following the Supreme Court’s landmark decision in Plessy v. Ferguson. Second, this Article recovers the lost story of the black women’s club movement’s response to race issues within the juvenile court movement. In doing so, this Article reconsiders the history of the national black women’s club movement within a new framework—that of black women as advocates for juvenile and criminal justice reform. Furthermore, a major issue that these child savers faced remains one that scholars of the juvenile court’s early history have not fully explored: race. Thus, this Article makes two main arguments. First, from its inception, the juvenile court perpetuated existing racial stereotypes about blackness and delinquency and enforced societal notions of race, gender and class stratification. Second, the National Association of Colored Women (―NACW‖) responded by placing criminal and juvenile justice issues as a major component of its civil rights agenda. From 1899 to 1930, the NACW’s efforts to challenge stereotypes about black delinquency impacted the development of the juvenile court system and its jurisprudence. NACW’s particular interest in juvenile justice sheds new light on how black female activists shaped the national discourse on race and crime and formulated their own strategies for juvenile justice reform.
Keywords: blackness; juvenile court; racial oppression; women; African-American; black women' s club movement